Synthesis of β‐Ketoiminato Copper(II) Complexes and Their Use in Copper Deposition. Issue 13 (22nd January 2020) - Preuß, Andrea; Korb, Marcus; Rüffer, Tobias; Bankwitz, Jörn; Georgi, Colin; Jakob, Alexander; Schulz, Stefan E.; Lang, Heinrich
Abstract : The template synthesis of ethylenediamine (1 ) with 2‐acetylcyclopentanone (2 ) and [Cu(OAc)2 · H2 O] (5 ) produced [Cu(1‐(2‐ c C5 H6 (O))C(Me)NCH2 )2 )] (6 ) in 82 % yield. Reaction of 5 with bis(benzoylacetone)diethylenetriamine (7, = L H) [1] gave [Cu(μ‐OAc)(L )(H2 O)]2 (8 ). The solid‐state structures of 6 and 8 were determined confirming that 8 possesses intra‐ and intermolecular hydrogen bonds resulting in a dimer formation. The thermal behavior of 6 –8 was studied by TG and TG‐MS. Under oxygen CuO was formed, whereas under Ar Cu/Cu2 O (6 ) or Cu (8 ) was obtained. Complex 6 was used as CVD precursor for Cu and Cu‐oxide deposition (substrate temp., 400–500 °C, N2, 60 mL· min –1 ; O2, 60 mL· min –1 ; pressure, 0.87–1.5 mbar). The as‐obtained deposits show separated particles of different appearance at the substrate surface as evidenced by SEM. Non ‐volatile 8 was applied as spin‐coating precursor for Cu and CuO formation [conc. 0.25 mol· L –1 ; volume 0.2 mL; 3000 rpm; depos. time 2 min; heating rate 50 K· min –1 ; holding time 60 min (Ar), 120 min (air) at 800 °C]. The samples on silicon consist of granulated particles (Ar) or are non‐dense with a grainy topography (air). EDX and XPS measurements confirmed the formation of Cu (Ar) or CuO (O2 ) with up to 13 mol‐% C impurity. Abstract :